Are patients being treated with immunosuppression for ocular inflammatory disease adequately?. (August 2015) - Cocho, Lidia; Swan, Robert T; Foster, Stephen C
<x xml:space="preserve">Abstract</x> Ocular inflammatory disease is often vision threatening to an individual, has significant socioeconomic impact to society and constitutes one of the more complex problems in ophthalmology. Adequate care of patients with ocular inflammatory disease requires enormous diagnostic and therapeutic efforts. Ocular immunologists need comprehensive training in several aspects of ophthalmology, and frequently, additional support from other specialties. Many reports have demonstrated the benefits of steroid-sparing agents in controlling inflammation and reducing the rate of adverse events, but it has to be stressed that poor adherence to current guidelines continues. The reasons for this are multifactorial, including unfamiliarity with the medications and concern for causing adverse events. We stress the importance of developing collaborations with rheumatologists, onocologists, allergists, dermatologists and infectious disease immunologists and adding trained ocular immunologists to faculty positions. In such ways, comprehensive ophthalmologists and those in training may gain comfort with steroid-sparing approaches to ocular inflammatory disease, reducing overreliance on chronic corticosteroids.